KEMAMPUAN MEMBACAKAN BERITA SISWA KELAS XI SMA N 1 PAINAN MENGGUNAKAN MEDIA AUDIO VISUAL - Vembriwazi, Ririt; Nisja, Indriani; Hartati, Yulia Sri (Pendidikan Bahasa Indonesia, 2014)
This research is motivated first, the lack of interest of students to read the news, zecond, students are in able to understand the elements that must be considered in reading the news, third, instructional methods used by teachers are less varied and monotonous. This study aimed to obtain a description of